Global warming-induced Asian hydrological climate transition across the Miocene–Pliocene boundary - Hong Ao (Nature Portfolio, 2021)
Global warming drove ‘wet gets wetter and dry gets drier’ climate shifts in Asia ~5.3 million years ago with monsoon pacing by ~400,000 and ~ 100,000 year cycles. This could be a template for future Asian climate response to anthropogenic warming.